#### Answer

$3-\sqrt{2},3,3+\sqrt{2}, 3+2\sqrt{2},3+3\sqrt{2}$

#### Work Step by Step

$\bf{\text{Solution Outline:}}$
To find the first $5$ terms, solve first the common difference. Then keep adding the common difference to the given second term.
$\bf{\text{Solution Details:}}$
The common difference is the difference between a term and the term before it. Hence, the common difference, $d,$ is
\begin{array}{l}\require{cancel}
d=a_2-a_1
\\\\
d=3-(3-\sqrt{2})
\\\\
d=3-3+\sqrt{2}
\\\\
d=\sqrt{2}
,\end{array}
Adding the common difference, the third term is
\begin{array}{l}\require{cancel}
a_3=a_2+d
\\\\
a_3=3+\sqrt{2}
,\end{array}
the fourth term is
\begin{array}{l}\require{cancel}
a_4=a_3+d
\\\\
a_4=3+\sqrt{2}+\sqrt{2}
\\\\
a_4=3+2\sqrt{2}
,\end{array}
and the fifth term is
\begin{array}{l}\require{cancel}
a_5=a_4+d
\\\\
a_5=3+2\sqrt{2}+\sqrt{2}
\\\\
a_5=3+3\sqrt{2}
,\end{array}
Hence, the first $5$ terms are $
3-\sqrt{2},3,3+\sqrt{2}, 3+2\sqrt{2},3+3\sqrt{2}
.$